ORGANIZATIONAL AND ECONOMIC MECHANISM FOR IMPROVING BUSINESS PROCESSES OF IT SECTOR ENTITIES IN THE CONDITIONS OF DIGITALIZATION OF THE ECONOMY - AVHUSTYN, Ruslan; DEMKIV, Iryna; BUDNIAK, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the issues of managing the development of entities in the IT sector of the national economy of Ukraine. It is argued that for this purpose, it is necessary to improve the management of their internal and external business processes through the implementation of a system of organizational and economic instruments, which are combined within a single holistic mechanism. That is why the purpose of the study is to form an organizational and economic mechanism for streamlining business processes of IT sector entities in the context of digitalization of the national economy of Ukraine. A model of the sequence of document formation for regulating the activities of an IT services entity under a process-oriented management system has been developed. It is indicated that the effective implementation of a process-oriented management system at IT services enterprises requires proper organization of management activities (the organizational component of the mechanism). The organizational support of this process includes, on the one hand, determining the persons responsible for planning, organizing, controlling and implementing procedural aspects of management, and on the other hand, developing regulatory documents. Implementation of a high-quality and effective mechanism for streamlining business processes of IT sector entities in the context of digitalization of the national economy also requires the implementation of measures aimed at motivating internal and external stakeholders of such processes, which will contribute to increasing their motivation and, consequently, making business and business processes more efficient (the economic component of the mechanism). It is concluded that the tools of the organizational and economic mechanism are formed in accordance with the classical management cycle, which covers the strategic, tactical and operational levels. The mechanism is based on structuring activities through the distribution of responsibility between personnel for the implementation of business processes, as well as monitoring efficiency based on key indicators. This approach ensures increased manageability of financial and economic activities, risk reduction, cost optimization and increased profitability.
Keywords: IT sector organizations; business processes; organizational and economic mechanism; IT market; digitalization; digitalization of the economy; ensuring efficiency; mechanism